Influence of torrefaction temperature and time on the yields and properties of torrefied biomass - Nigran Homdoung (2019)
© 2019, Paulus Editora. All rights reserved. Thailand has great potential to use biomass from agricultural wastes for renewable fuels and energy. However, its current utilization is rather low due largely to the high moisture content and low energetic density of these materials. A simple thermal pretreatment such as torrefaction may be useful in adding value to these solid agricultural wastes. The objective of this work was to investigate effect of torrefaction temperature and time on the yields and physico-chemical properties of agricultural wastes (wood chips and oil palm fronds). The torrefaction experimental work was carried out in a laboratory reactor with varying temperatures of 200 to 400 °C and reaction times of 20 to 60 min. A 5 kW electrical heater was used to heat the reactor. From the results obtained, it was found that torrefaction temperature and time affected the solid product proximate and energy properties. The higher heating value of torrefied fuel was increased with torrefaction temperature and time. Optimum torrefaction temperature for wood chips and oil palm fronds was identified at 200 °C, while optimum times were 20 and 40 min, respectively, for maximum mass and energy yields. At these conditions, the energy content of both biomass materials was improved to 17.65 MJ/kg and 16.34 MJ/kg, 20-30% higher than the original values. The value and energy yield of wood chips and oil palm fronds could be improved through torrefaction.